Health Journalism: A Unique Specialty in Nepal - Singh , Yogendra P (Journal of Institute of Medicine Nepal, 2023)
Health Journalism is both science and art. Journalism is the concept of providing well-balanced information to the public. It must be a natural way of description so that everyone can understand. It is different from medical writing which is usually complex and peers review publications. Health journalism is reporting on health research, medical news, and scientific breakthroughs to the public.